(untitled) (Journal of Oriental Studies, 2016)
The article deals with the study by Sh.Ualihnov the map data for Japan. The authors clarified aspects of mapping by Sh.Ualihnov some localities of provinces of the Land of the Rising Sun. They also compared the information entered by scientist and modern disposition of these settlements.